Disease burden concerning hepatitis E-infected inpatients in Jiangsu province, China. Issue 3 (16th January 2020) - Cui, Tingting; Zhang, Xuefeng; Wang, Qiang; Yue, Na; Zheng, Mengyun; Wang, Donglei; Duan, Chunxiao; Yu, Xiaoge; Bao, Changjun; Jiang, Renjie; Xu, Shilin; Yuan, Zhaohu; et al.
Abstract: Objective: This study aimed to determine the disease burden of hepatitis E virus (HEV)-infected inpatients in Jiangsu province, China. Methods: Between July 1, 2016 and October 31, 2018, 1152 HEV-infected inpatients were identified from four cities in Jiangsu province, namely, Nanjing, Suzhou, Yancheng, and Zhenjiang. The disease burden comprised the economic burden and loss of health due to HEV infection. Factors influencing the disease burden were analyzed using univariate and multivariate analyses. Results: The average direct, indirect, and total economic burden for 1152 HEV-infected inpatients was US$ 4, 986.40, US$ 1, 507.28, and US$ 6, 493.68, respectively, accounting for 46.66%, 14.11%, and 60.77% of per capita disposable income (PCDI) in Jiangsu province, respectively. The disease burden for HEV-infected inpatients with hepatitis B was significantly higher than that for other inpatients. The average EQ-5D utility value of 1152 HEV-infected inpatients was 0.72 ± 0.18 quality-adjusted life years (QALYs) and the average EQ-visual analogue score (EQ-VAS) was 0.66 ± 0.17 points. Multivariate analysis showed that the direct economic burden and the total economic burden were influenced by variables such as hospitalization days, outcomes, past history of other diseases, and regions ( P  < 0.05). It was estimated the direct economic burden, the indirect economic burden, and the total economic burden for all HEV-infected inpatients in Jiangsu province in 2018 was approximately US$ 9.2 million, US$ 2.8 million and US$ 12.0 million, respectively. Conclusion: The disease burden of HEV infection in Jiangsu province is severe, and more attention should be paid to the prevention of hepatitis E and the treatment of comorbidities.